Kajian Normalisasi Terhadap Kapasitas Sungai Gude Desa Pulolor Berbasis HEC-RAS - Armanda Beta Saputra; Danayati Azmi Dewi Nusantara (Institut Teknologi Adhi Tama Surabaya, 2021)
Floods that occur due to the overflowing of Gude River are the main problem in Jombang Regency. Gude River is a river with a length of 8.67 km that flows from Gudo sub-district behind the Sengfong company which is split into the Gude Denanyar River and the Gude Ploso River. This study discusses the normalization of Gude River capacity at a 20 year return period using HEC-RAS software. In this study, the method used to calculate the design flood is Nakayasu unit synthetic hydrograph and the HEC-RAS software for flow simulation modeling. The calculation result of the flood discharge with a return period of 2 years is 76,89 m3/sec, at 5 years it is 91,59 m3/sec, at 25 years it is 113,62 m3/sec, at 50 years it is 122,75 m3/sec, and at 100 years is 131,80 m3/sec. Based on the discharge data and topographical data of Gude River that has been inputted at the HEC-RAS, it shows that the overflow occurs in almost all river cross sections except at Sta 0, Sta 14, and Sta 17. Normalization can be carried out to overcome the overflow of Gude River, by dredging sedimentation as deep as 1,5 meters and constructing embankments on both sides of the river with a height of 1.3 meters.